Energy and exergy analysis of a ground-coupled heat pump system with two horizontal ground heat exchangers - Esen, Hikmet; Inalli, Mustafa; Esen, Mehmet; Pihtili, Kazim (Pergamon-Elsevier Science Ltd, 2007)
In this paper we investigate of energetic and exergetic efficiencies of ground-coupled heat pump (GCHP) system as a function of depth trenches for heating season. The horizontal ground heat exchangers (HGHEs) were used and it were buried with in 1 in (HGHE1) and 2m (HGHE2) depth trenches. The energy efficiency of GCHP systems are obtained to 2.5 and 2.8, respectively, while the exergetic efficiencies of the overall system are found to be 53.1% and 56.3%, respectively, for HGHE1 and HGHE2. The irreversibility of HGHE2 is less than of the HGHE1 as about 2.0%. The results show that the energetic and exergetic efficiencies of the system increase when increasing the heat source (ground) temperature for heating season. And the end of this study, we deal with the effects of varying reference environment temperature on the exergy efficiencies of HGHE1 and HGHE2. The results show that increasing reference environment temperature decreases the exergy efficiency in both HGHE1 and HGHE2. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: ground coupled heat pump; horizontal ground heat exchanger; energy analysis; exergy analysis